(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Sculptors have always been working with and for the environment. Unlike other fields of Fine Art that are slowly entering digital and virtual space, sculptures still largely tend to be made with and displayed within nature. During prehistoric times artists discovered animal bones, stone and wood as their sculpting material. With time they discovered baked clay, even further they went on to explore metals, and made alloys. Newer ages gave rise to industrial materials like cement, ceramic and fiberglass, and artists adapted themselves to the material they felt would help them express. With their hands on approach and understanding of the marvels that mother earth provided to them, they managed to make these materials into mediums. They explored how these materials came into existence, observed properties like textures, durability, or strength and forged tools and techniques to express through them. A sculptor’s choice of material is often one of the most crucial decisions of any art making process.